KEPEMIMPINAN KEPALA MADRASAH DALAM PENINGKATAN MUTU PENDIDIKAN - Harahap, Rossa Hadana; Syafaruddin, Syafaruddin; Siahaan, Ahmad Taufik Al Afkari (Prodi PGMI STIT Al-Ittihadiyah Labuhanbatu Utara, 2021)
Educational leadership has a strategic role in improving the quality of education. Therefore, the quality of educational leadership needs to be improved in realizing the achievement of educational goals effectively and efficiently. The higher the quality of leadership in schools, it is expected that the process of influencing the resources of educators and education personnel to produce higher performance is also expected. In this way, the increase in the achievement of educational customer expectations is also increasing within the framework of satisfaction of parties related to education.